2015
DOI: 10.1007/s00792-015-0759-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in understanding the molecular mechanisms of radioresistance in Deinococcus bacteria

Abstract: The deleterious effects of ionizing radiation are a major concern of the modern world. In the last decades, outstanding interest has been given to developing new therapeutic tools designed for protection against the toxic effects of ionizing radiation. Deinococcus spp. are among the most radioresistant organisms on Earth, being able to survive extreme doses of radiation, 1000-fold higher than most vertebrates. The molecular mechanisms underlying DNA repair and biomolecular protection, which are responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 111 publications
0
30
0
Order By: Relevance
“…It has been suggested that the proteome of D. radiodurans is well-protected by the antioxidant system after exposure to IR [7,14]. The undamaged proteins perform their function of repairing injured cellular macromolecules (DNA, lipids, and proteins), ultimately restoring the cell to its normal physiological state.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the proteome of D. radiodurans is well-protected by the antioxidant system after exposure to IR [7,14]. The undamaged proteins perform their function of repairing injured cellular macromolecules (DNA, lipids, and proteins), ultimately restoring the cell to its normal physiological state.…”
Section: Discussionmentioning
confidence: 99%
“…Humans have evolved from single cell ancestors and as a species, have grown amongst a world teeming with microorganisms. From scalding volcanic vents in deep oceans to radioactive surroundings, microorganisms not only occupy the outside world but also exist in our internal organs, such as the GI tract (7,8). Microbiota refers to "the ecological community of commensal, symbiotic, and pathogenic microorganisms that share our body space."…”
Section: Humans and Microorganismsmentioning
confidence: 99%
“…Various enzymatic and non-enzymatic anti-oxidative systems, redundancy in DNA repair genes with a unique DNA repair machinery called extended synthesis dependent strand annealing (ESDSA), and some physical characteristics of nucleoids, which are advantageous to DNA repair, contribute to the extreme resistance of D. radiodurans (Ishino and Narumi, 2015; Munteanu et al, 2015). However, the precise mechanisms governing the multiple resistance characteristics of this organism remain unclear.…”
Section: Introductionmentioning
confidence: 99%